Insights into the differential fragmentation processes in rock avalanche emplacement from field investigation and experimental study - Wang, Yu-Feng; Cheng, Qian-Gong; Lin, Qi-Wen; Li, Kun; Ji, Yan-Dong (Frontiers in Earth Science, 2022)
Fragmentation is a universal phenomenon reported in rock avalanches with an abundance of complex sedimentological structures being resulted, which can provide insights into rock avalanche emplacement processes if studied in detail. To further explore the emplacement processes of rock avalanches, six typical cases are carefully studied with an analogue study being designed and conducted. It is reached that the carapace facies is characterized by clast-supported structures composed of large blocks with some sedimentological structures, including retained stratigraphic sequences, imbricate structures and jigsaw structures. The body facies presents a higher degree of fragmentation with block-rich zones, fine matrix-rich zones, jigsaw structures, and inner shear zones. The basal facies displays a highest degree of fragmentation, which is mainly composed of millimeter grains with thin shear strips formed. Consistent with the field investigations, differential fragmentation in vertical was also observed in the analogue tests with the carapace facies mainly fragmented along the pre-existing structures, the body facies fragmented with abundance of new fractures generated and the basal facies fragmented into fine grains. Meanwhile, preserved layer sequences in longitudinal and vertical profiles are also observed in the analogue tests, indicating a low disturbance in the propagation. Therefore, we propose that a process characterized by a sparse state dominated by collisions, minor disturbance and pervasive dynamic fragmentation likely occurs in the carapace facies with fragmentation mainly controlled by the breakage of pre-existing, fully persistent structures. The body facies is mainly controlled by the fracturing of the weak, less-persistent structures and the basal facies displays a highest degree of fragmentation with abundance of new fractures generated. In the whole propagation, the avalanche mass displays a low-disturbed laminar flow.